Dimensions of leisure for life individuals and society (Human Kinetics, 2010)
From both an individual and a societal perspective, Dimensions of Leisure for Life guides students through a study of leisure as a multidisciplinary field. The book uses social sciences methods and current research, with examples from psychology, geography, anthropology, and sociology, to study leisure behavior. With contributions from 23 leading professors, the book examines the following: The concept of leisure, including the various ways in which it has been defined and described, the benefits associated with it, the scope of the leisure industry field, and the basis for studying leisure as a social science The impact of leisure on quality of life, health, physical activity and stress levels, and overall happiness and well-being The social significance of leisure, including the interaction of leisure with history, contemporary society, technology, the environment, economics, and politics and public policy The factors that influence each individual's leisure choices and level of involvement in leisure activities, such as awareness of local options; barriers of age, gender, sexual orientation, race, ethnicity, religion, or socioeconomic status; geographic distribution of leisure spaces; and maturity level and stage of development. Students will also consider the part that recreation and leisure play in their own lives. Dimensions of Leisure for Life will guide them on a search for new leisure experiences, starting with their campus and moving on to the wider community and beyond. They'll search out the resources that are available to them, learn to recognize and challenge the obstacles to participation, and commit to a leisure plan that will meet their needs and enhance personal growth. They will also examine contemporary issues, such as active living, work-to-life balance, the environmental impact of leisure, and sustainability, and discuss how these issues could influence their leisure activity choices.